Novel Resveratrol-chalcone Derivatives: Synthesis and Biological Evaluation - Ma, Yulu; Zheng, Xi; Zhu, Ping; Liu, Bei; Gao, Hui; Mao, Zewei; Zhang, Lijun; Wan, Chunping (Mini Reviews in Medicinal Chemistry, 2019)
Introduction: Resveratrol and chalcones are lead compounds with good biological activities. Method: In this study, a series of novel derivatives (6-38) between resveratrol and chalcone possessing piperazine moiety have been synthesized, and in vitro anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated RAW-264.7 macrophages and anti-proliferative effect on a panel of human tumor cell lines (Hela, A549 and SGC7901) by MTT assay were evaluated. Result: The results demonstrated that the substituents of the NH group of piperazine ring had an obvious influence on biological activities. Especially, compounds 13, 17, 30, 31 and 36 showed good inhibitory effect on the generation of NO compared to dexamethasone. Furthermore, analogs 20, 21, 22 and 25 were found to be the better anti-proliferative effect on 3 human tumor cell lines, which were found to be a better cytotoxic activity to positive control 5-FU. Many compounds displayed low cytotoxic effect on normal cells L02. Conclusion: Further FACs analysis showed that compounds 20 and 25 significantly induced apoptosis in A549 cell. These derivatives were considered as the potential anti-inflammatory and anti-tumor agents.
Keywords: Resveratrol